Administrative management of research projects in institutions of higher education (2014)
The modernization of higher education institutions involves the transformation of its management, as well as changes in internal relations and the environment. You need flexible structures, making them lighter and promote schemes that ensure greater commitment of all agencies of the Public Educational Institutions of Higher Education, streamlining internal processes.